2006
DOI: 10.1111/j.1538-7836.2006.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of low levels of factor VIII or factor IX in hemophilia A and hemophilia B plasma by clot waveform analysis and thrombin generation assay

Abstract: Summary. Background: Precise assessment of clotting function is essential for monitoring of hemostatic treatment for hemophilias A and B. Materials and methods: Clot waveform analysis and thrombin generation assays were performed on factor (F) VIII-and FIX-deficient plasmas, which had been reconstituted with known amounts of recombinant FVIII (rFVIII) and affinity-purified FIX respectively. Clot waveforms were assessed qualitatively and quantitatively by measuring the parameters clotting time, maximum coagulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 16 publications
(21 reference statements)
7
104
0
1
Order By: Relevance
“…The ETP appears to have low sensitivity, however, and we have found that results obtained with the TGT (in particular, ETP) do not correlate with lower levels of FVIII:C [10]. In contrast, CWA parameters seemed to provide a better correlation between clinical symptoms and very low levels of FVIII:C [13]. In the present study, we have demonstrated that the CWA parameters (CT, |min1|, and |min2|) can provide very useful quantitative information for the monitoring of hemostasis during treatment with rFVIIa and APCC, and for the perioperative management of this type of inhibitor-bypassing therapy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The ETP appears to have low sensitivity, however, and we have found that results obtained with the TGT (in particular, ETP) do not correlate with lower levels of FVIII:C [10]. In contrast, CWA parameters seemed to provide a better correlation between clinical symptoms and very low levels of FVIII:C [13]. In the present study, we have demonstrated that the CWA parameters (CT, |min1|, and |min2|) can provide very useful quantitative information for the monitoring of hemostasis during treatment with rFVIIa and APCC, and for the perioperative management of this type of inhibitor-bypassing therapy.…”
Section: Discussionmentioning
confidence: 62%
“…The data obtained from this assay reflect the overall process of hemostasis, including fibrinolytic activity. Shima et al have demonstrated that there are several advantages to the use of CWA in HA patients without inhibitors [12,13]. In addition, recommendations on the standardization and clinical application of this assay have recently been reported by the Scientific and Standardization Committee of the ISTH [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ETP and peak height generally correlated with FVIII levels, 17 there was a very large variation in these parameters at higher FVIII levels, with ETP ranging from 50 to 160% at FVIII levels of approximately 100%. While correlations were around R=0.79 for the group as a whole, patients showed much narrower intra-individual variation with very high correlations when studied individually.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, time to peak was correlated with FVIII levels. 17 The only study available on thrombin generation after in vivo FVIII administration in a platelet-poor plasma assay was recently published by Lewis et al, 18 who used a 1 pM tissue factor stimulus. In this study, the ETP and peak height of the thrombin generation curve show wide inter-and intraindividual variations, indicating that other components of coagulation or inhibition thereof are involved besides FVIII.…”
Section: Introductionmentioning
confidence: 99%
“…In diseases marked by hypocoagulation, such as hemophilia A and B, which are characterized by the generation of low levels of factors VIII and IX, respectively [3], clotting time is prolonged leading to excessive bleeding due to lower levels of generated thrombin. The role of thrombin and prothrombin in proteolysis of microtubule associated tau protein in the brain has been studied as well and hypothesized to be important in the development of Alzheimer's disease and Parkinsonism dementia of Guam [4].…”
Section: Introductionmentioning
confidence: 99%